2020
DOI: 10.1021/acs.chemrestox.0c00086
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Fundamental Chemical Toxicology Research To Inform Medical Countermeasure Developments: The National Institutes of Health Chemical Countermeasures Research Program

Abstract: A high-consequence chemical emergency is a major public health concern. In the United States, the National Institute of Allergy and Infectious Diseases within the National Institutes of Health pioneers discovery and early development of critical medical countermeasures against chemical threats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Traditionally, chemical, biological, radiological, and nuclear agents were viewed as threats to only the military until the events of September 11, 2001, and the anthrax mailing incidents in October 2001. These incidents, as well as the sarin attacks in Tokyo and Syria, VX attacks in Malaysia, and Novichok attacks in England revealed the vulnerability of civilians to unconventional terrorism threats such as nerve agents (Morita et al, 1995;Suzuki et al, 1995;Okumura et al, 1996;Miyaki et al, 2005;Yanagisawa et al, 2006;Zarocostas, 2017;Jett et al, 2020;Yeung et al, 2020). Until recently, preventing acute deaths due to OPNA exposure had taken a top priority.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, chemical, biological, radiological, and nuclear agents were viewed as threats to only the military until the events of September 11, 2001, and the anthrax mailing incidents in October 2001. These incidents, as well as the sarin attacks in Tokyo and Syria, VX attacks in Malaysia, and Novichok attacks in England revealed the vulnerability of civilians to unconventional terrorism threats such as nerve agents (Morita et al, 1995;Suzuki et al, 1995;Okumura et al, 1996;Miyaki et al, 2005;Yanagisawa et al, 2006;Zarocostas, 2017;Jett et al, 2020;Yeung et al, 2020). Until recently, preventing acute deaths due to OPNA exposure had taken a top priority.…”
Section: Discussionmentioning
confidence: 99%
“…The AR approval relies on adequate and well-controlled studies in relevant animal models to determine efficacy of the MCM as well as extensive safety studies in human volunteers. The foundational pillars of the AR necessitate (1) a well-understood pathophysiology sequelae of the insult/injury (chemical, biological, radiological) and its resolution by the MCM, (2) efficacy in more than one animal model predictive of response in humans, (3) study endpoints related to desired benefits in humans (reduction in major morbidity or mortality), and (4) pharmacokinetic (PK)/ pharmacodynamic (PD) assessments in animal models and humans that allow for appropriate MCM dose scaling.…”
Section: Fda Requirementsmentioning
confidence: 99%
“… 1 This trans-NIH partnership allows the CCRP to capitalize on relevant subject matter expertise in pulmonary, dermal, ocular, and neurological research that already exists at the respective NIH institutes and their extramural communities. 2 The CCRP at the NIAID is responsible for overall execution of the NIH Strategic Plan and Research Agenda for Medical Countermeasures Against Chemical Threats ( www.niaid.nih.gov/sites/default/files/NIH-Strategic-Plan-and-Research-Agenda200708.pdf ) and provides over-sight and funding to various R21, R01, R34, UG3/UH3, and Small Business research grant and cooperative agreement initiatives administered by partner ICs, including the Countermeasures Against Chemical Threats (CounterACT) translational program.…”
Section: Introductionmentioning
confidence: 99%
“…The cornea is the most exposed mucosal surface of the eye, and as such, corneal epithelial cells are the main focus in in vitro cell culture models for ocular toxicity (Ronkko et al 2016;Yeung et al 2020). More than 30 yr ago, it was demonstrated that the corneal epithelium is renewed constantly by limbal epithelial stem cells that migrate from the corneo-scleral junction, known as the limbus (Schermer et al 1986).…”
Section: Source Of Corneal Epithelial Cellsmentioning
confidence: 99%